Taxonomy and genetic diversity of mullets (family: mugilidae) of Kerala - Rahul, R. (KUFOS, 2019)
The family Mugilidae collectively known as grey mullets comprise 27 genera and 78 species, mainly confined in different aquatic coastal habitats in tropical, subtropical and temperate regions of the world (Thomson 1966; Nelson 2006; Nelson 2016; Durand et al.2012). It is remarkably difficult to resolve species limits between closely connected fish species or families defined by morphological uniformity as in the case of mugilidae. Poor taxonomic evaluation of Mugilidae is very prominent because of their conservative morphology and paucity of useful taxonomic characters (Menezes, 1983; Gilbert, 1993; Thomson, 1997). Species with circum globular distribution like Mugil cephalus possess cryptic behaviour, also a major factor which limits the classical morphometry. So, in order to resolve the taxonomic ambiguity prevails in the mugilds an integrative taxonomic approach is needed. This study was carried out to determine the taxonomy (morphological and molecular) of mullets from Kerala. A total of 253 specimens were collected from 16 locations in Kerala and morphometric and meristic data were recorded of the same. Out of 253 individuals mitochondrial co1 gene of 38 specimens were coded. Based on the obtained sequences a phylogenetic tree was constructed. Seven species under four genera (Planiliza,Osteomugil,Crenimugil and Mugil) were recognized. Planiliza subvirids, Osteomugil perusii, Mugil cephalus, Planiliza cf. macrolepis and unrecognized species of Planiliza, Crenimugil and Osteomugil genus identified from Kerala. Further studies using multiple genes, osteology, anatomy should be carried out to improve our understanding of the diversity and distribution of Mugilid species from Kerala.